The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1969
DOI: 10.1029/wr005i004p00749
|View full text |Cite
|
Sign up to set email alerts
|

A Game Theory Approach to the Problems of International River Basins

Abstract: The lower Garages and the Brahmaputra rivers flow out of India and join together in the province of East Pakistan to form one of the major river systems in the world. Each year the rivers flood during the monsoon, causing loss of life and great damage to crops and property. The problem is further exacerbated by the fact that the best flood control points in the basin are not under the political control of Pakistan, which suffers most from the floods. The number of possible combinations of structural and nonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0
1

Year Published

1976
1976
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(60 citation statements)
references
References 1 publication
1
58
0
1
Order By: Relevance
“…The first order interior conditions for the problem faced by country 2 similarly result in: From equation (9) we see that country 1 sets its pollution tax equal to the marginal damage incurred solely from the salination level within its own boundary. Equation (10) demonstrates that country 1 produces abatement up to the level that equates marginal benefit and cost from abatement.…”
Section: Noncooperative Benchmark Equilibriummentioning
confidence: 99%
See 1 more Smart Citation
“…The first order interior conditions for the problem faced by country 2 similarly result in: From equation (9) we see that country 1 sets its pollution tax equal to the marginal damage incurred solely from the salination level within its own boundary. Equation (10) demonstrates that country 1 produces abatement up to the level that equates marginal benefit and cost from abatement.…”
Section: Noncooperative Benchmark Equilibriummentioning
confidence: 99%
“…For example, Rogers (1969) formulates a cooperative game of water allocation for the Ganges and Nile rivers and shows how cooperation leads to a Pareto efficient allocation. Hardin (1968) provides an explanation of the "tragedy of the commons", which explains why water resources are sometimes heavily overexploited because of noncooperation among competing users.…”
Section: Introductionmentioning
confidence: 99%
“…The first application of game theory is designed to show the potential advantages of coalition in the integrated water resources basin development over the case of the Ganges Brahmaputra Basin [Rogers, 1969]. Later, Rogers [1993] outlined possible alternative allocation models that can be employed in the transboundary water resources allocation issues.…”
Section: Introductionmentioning
confidence: 99%
“…Game theoretic analysis of riparian nation interactions over water date back at least to Rogers (1969), who showed that cooperation was not a Nash equilibrium for the game between India and Bangladesh. Dinar and Wolf (1994) compared a range of alternatives for regional water trade between Egypt and Israel/Palestine, arguing that the set of acceptable arrangements had to consider the political as well as the economic relationships involved.…”
Section: Introductionmentioning
confidence: 99%
“…Many such cases, both inter-and intra-national, are documented in Dinar and Loehman (1995) and Parker and Tsur (1997), where various approaches to facilitating greater cooperation are also discussed. Rogers (1969) evaluated several infrastructure investment patterns for the Ganges and Brahmaputra rivers shared by India and Bangladesh. Jointly optimal development plans were identified, but it was shown that these were not welfare maximizing for India, the upstream nation, and therefore unlikely to be implemented.…”
Section: Introductionmentioning
confidence: 99%